Pengembangan Usaha Masyarakat Melalui Pelatihan Inovasi Produk Berbahan dasar Tepung Tempe sebagai pengganti Tepung Terigu di Desa Setiamekar - Dhiani, Dhiani; Farrah, Farrah; Suesilowati, Suesilowati (Bulletin of Community Engagement, 2023)
To Improfing knowledge among Micro, Small Medium Enterprise (MSMEs) actors in Setiamekar Village, Tambun Selatan District, Bekasi toward using of tempeh as a profitable business opportunity, they also need to improve knowledge about other products that using tempeh as the basic ingredient. The methods used include socialization, mentoring, and practice in creating innovative processed tempeh products. This type of product is produced from the basic ingredient of tempeh which will later be transformed into tempeh flour and will be processed into a variety of snacks that are delicious, healthy, attractive and have sales value, namely Gluten Free Brownies Cookies. The result of the training activities carried out is the success of MSMEs in Setiamekar Village in processing innovative and creative products that use tempeh as the basic ingredient as a profitable business opportunity, increasing the selling value of tempeh, and as an effort to extend the shelf life of tempeh. Keywords: Tempeh Flour, MSMEs, Gluten Free Diet, Product Innovation Training